Organic-walled microfossils of the mid-Neoproterozoic Alinya Formation, Officer Basin, Australia. (14th September 2016) - Riedman, Leigh Anne; Porter, Susannah
Abstract: Estimates of Precambrian eukaryotic diversity and disparity indicate broad trends of increase in the Mesoproterozoic Era, leading to a peak and then rapid decline by ca. 750 Ma. The organic-walled microfossil assemblage presented here is representative of that mid-Neoproterozoic height of eukaryotic species richness. Organic-rich shales and siltstones of the mid-Neoproterozoic upper Alinya Formation, eastern Officer Basin, Australia, preserve an abundant and diverse assemblage of organic-walled microfossils deposited in a low-latitude, shallow marine setting. Use of scanning electron microscopy (SEM) revealed an unexpected level of morphological detail not visible in transmitted light microscopy. This led to the recognition of new species as well as establishment of degradational sequences, which aid in fossil recognition. In total, 26 taxa are described here; these include 21 previously named forms, four newly described species ( Caelatimurus foveolatus, Culcitulisphaera revelata, Karenagare alinyaensis, and Morgensternia officerensis ), and one new combination ( Vidalopalla verrucata ).